Protozoan plankton ecology - Laybourn-Parry Johanna (London Chapman & Hall, 1992)
This text looks at the biology, temporal and spatial distribution patterns and the functional role of planktonic protozoa in fresh, brackish and marine waters. In recent years the importance of these organisms in ecological processes such as the flow of
Keywords: Ecology; Protozoa; Zooplankton